2006
DOI: 10.1002/jcb.20906
|View full text |Cite
|
Sign up to set email alerts
|

Existence of autocrine loop between interleukin‐6 and tranforming growth factor‐β1 in activated rat pancreatic stellate cells

Abstract: Interleukin (IL)-6 is a proinflammatory cytokine assumed to participate in pancreatic fibrosis by activating pancreatic stellate cells (PSCs). Autocrine TGF-beta1 is to central in PSC functional regulation. In this study, we examined IL-6 secretion from culture-activated rat PSCs and its regulatory mechanism. Activated PSCs express and secrete IL-6. When anti-TGF-beta1 neutralizing antibody was added in the culture medium, IL-6 secretion from activated PSCs was inhibited, whereas exogenous TGF-beta1 added in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…8), suggesting a pivotal role of the TGF-␤1-Smad2 signaling pathway in SPC-induced SMC differentiation. Accumulating evidence demonstrates that expression of TGF-␤1 can be induced by various cytokines, including IL-1␤, IL-6, and IL-10 and angiotensin II (Aoki et al, 2006b;Aoki et al, 2006a;Sinuani et al, 2006;Wang et al, 2006), and that the IL-1␤- and IL-6-induced expression of TGF-␤1 is mediated by an ERK-dependent pathway (Aoki et al, 2006b;Aoki et al, 2006a). Moreover, angiotensin II induces the late activation of Smad2/3 by an ERK-dependent pathway, and angiotensin IIinduced secretion of TGF-␤1 is responsible for the activation of Smad2/3 in vascular SMCs (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…8), suggesting a pivotal role of the TGF-␤1-Smad2 signaling pathway in SPC-induced SMC differentiation. Accumulating evidence demonstrates that expression of TGF-␤1 can be induced by various cytokines, including IL-1␤, IL-6, and IL-10 and angiotensin II (Aoki et al, 2006b;Aoki et al, 2006a;Sinuani et al, 2006;Wang et al, 2006), and that the IL-1␤- and IL-6-induced expression of TGF-␤1 is mediated by an ERK-dependent pathway (Aoki et al, 2006b;Aoki et al, 2006a). Moreover, angiotensin II induces the late activation of Smad2/3 by an ERK-dependent pathway, and angiotensin IIinduced secretion of TGF-␤1 is responsible for the activation of Smad2/3 in vascular SMCs (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For simplicity, we assumed that the cytokines are produced (by PSCs or macrophages) at a constant rate, and they undergo a natural decay with constant rates (9,10,24,25,27). However, in the production of IL-6, we also included enhancement of IL-6 production by TGF-β (24).…”
Section: Mathematical Modelmentioning
confidence: 99%
“…During pancreatic inflammation, endothelial cells secrete monocyte chemoattractant protein (MCP-1) (14-19), triggering recruitment of monocytes from the blood into the inflamed area (20,21). Upon entering the pancreas, monocytes differentiate into macrophages, which secrete tumor necrosis factor alpha (TNF-α) (22,23) and interleukin 6 (IL-6) (24,25). TNF-α and IL-6 from macrophages, along with other soluble factors, are then capable of causing PSC activation.…”
mentioning
confidence: 99%
“…It has been proposed that an autocrine loop exists between TGF-b1 and IL-1b through Smad3-and ERK-dependent pathways [74]. Another autocrine loop may exist between IL-6 and TGF-b1 through ERK-and Smad2/3-dependent pathways in activated PSCs [75]. Interestingly, it has been recently shown that cyclooxygenase-2 expression, induced by TGF-b1 through Smad2/ 3-dependent pathways, is required for activated PSCs to respond to proinflammatory cytokines [19].…”
Section: Janus-activated Kinases (Jak)/signal Transducers and Activatmentioning
confidence: 99%